2020
DOI: 10.1111/os.12643
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Thoracolumbar Fractures Through Different Short Segment Pedicle Screw Fixation Techniques: A Finite Element Analysis

Abstract: Objective: To compare the von Mises stresses of the pedicle screw system and the displacement of injured vertebrae using 3-D finite element analysis, and to evaluate the curative effect of the pedicle screw system. Methods:Finite element methods were used for biomechanical comparison of four posterior short segment pedicle screw fixation techniques. The different pedicle screw models are traditional trajectory (TT), Universal Spine System (USS), cortical bone trajectory (CBT), and CBT at the cranial level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…We found that the site with the largest VMS in internal fixation was at the screw-rod connection site in all models, explaining why internal fixation is prone to failure at the screw-rod connection site. Similar findings were reported previously [ 21 23 ]. PUVCR showed slightly higher screw and rod stresses than VCR in all loading cases except in short-segment lateral bending.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the site with the largest VMS in internal fixation was at the screw-rod connection site in all models, explaining why internal fixation is prone to failure at the screw-rod connection site. Similar findings were reported previously [ 21 23 ]. PUVCR showed slightly higher screw and rod stresses than VCR in all loading cases except in short-segment lateral bending.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the site with the largest VMS in internal xation was at the screw-rod connection site in all models, which explains why internal xation is prone to failure at the screw-rod connection site. Similar ndings were reported previously [21][22][23]. PUVCR showed slightly higher screw and rod stresses than VCR in all loading cases except in short segment lateral bending.…”
Section: Discussionsupporting
confidence: 91%
“…However, the results of each study were inconsistent, so the difference between CBT screw implantation and traditional pedicle screws was still worth discussing. A finite element analysis model of a CBT screw combined with a traditional pedicle screw was also established [19]. The biomechanical evaluation was compared with the CBT screw system, traditional pedicle screw system, and universal spine system.…”
Section: Introductionmentioning
confidence: 99%